Tawba Al-Khafaji: His Political Confrontations & Invasion during the Umayyad Era - Jasim, khudir; Naser, Adhraa (International Journal of History Research, 2023)
Purpose: The purpose of the study is to explore the life of Tawba Al-Khafaji in his political confrontations and invasion during the Ummayyad. Methodology: The study desktop literature research design. Findings: Tawba was an opposing and dissenting man to the Umayyad state and out of its law Unique Contribution to Theory, Practice and Policy: To conclude Tweba was one of the fiercest men in the history of Arabs and had fights and duels with some of the most famous men of literature and poetry being the best and the defeater as mentioned in the history of Arabs literature.